INTERVENÇÃO DO ASSISTENTE SOCIAL NO CONTEXTO DE PREVENÇÃO AO ABANDONO ESCOLAR (REMUNOM, 2024)
Despite this fact, the presence of social workers in schools still presents a social gap. This research study is the result of a bibliographic study. Thus, social aspects regarding school dropout in public basic education in Brazil will be explored. The objective is to develop a basic qualitative research using bibliographic and documentary research methods in order to enrich the data presented by the documentary survey. The daily and operational tasks of Social Work in the current educational system will be discussed. Additionally, the meaning of school dropout for Social Work will be studied, as well as the means of intervention by social workers from a sociocultural perspective, emphasizing the integration of the social worker in schools.Keywords: Separadas por ponto e vírgula.Keywords: School Dropout. Basic education. Social Intervention in Basic Education. Social Work